Nowcasting Australia's gross domestic product - Angelia L. Grant (The Australian Government, The Treasury, 2018)
This paper adopts the methodology developed by the Federal Reserve Bank of Atlanta to nowcast the expenditure components of Gross Domestic Product (GDP) for the Australian economy. The aim is to help assess the current state of the economy and to assist with macroeconomic forecasting. A range of partial indicators and financial market data are used to estimate a dynamic factor, with the estimated factor then used to nowcast relevant partial indicators. These nowcasts of partial indicators are used to nowcast each expenditure component of GDP. The nowcasting framework is found to be a valuable tool in assessing the current state of the economy.
Keywords: C32; C53; E17; E30; 330; Nowcasting; Gross Domestic Product; dynamic factor model